2017
DOI: 10.1007/978-3-319-53889-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Huntington’s Disease

Abstract: Huntington's disease (HD) is a genetic, fatal autosomal dominant neurodegenerative disorder typically occurring in midlife with symptoms ranging from chorea, to dementia, to personality disturbances (Philos Trans R Soc Lond Ser B Biol Sci 354:957-961, 1999). HD is inherited in a dominant fashion, and the underlying mutation in all cases is a CAG trinucleotide repeat expansion within exon 1 of the HD gene (Cell 72:971-983, 1993). The expanded CAG repeat, translated into a lengthened glutamine tract at the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 124 publications
0
40
0
Order By: Relevance
“…Besides the nuclear DNA, there is growing evidence that the mitochondrial DNA (mtDNA) could be controlled by epigenetic mechanisms (Hroudová et al, 2014;Blanch et al, 2016;Stoccoro et al, 2017). Several studies have demonstrated the impact of epigenetic modifications on the pathogenesis of neurodegenerative diseases (Urdinguio et al, 2009;Gruber, 2011;Gangisetty and Murugan, 2016;Bassi et al, 2017;Smith and Lunnon, 2017;Berson et al, 2018;Gangisetty et al, 2018;Lardenoije et al, 2018;Lascano et al, 2018;Qazi et al, 2018;Stoccoro and Coppedè, 2018). There is a growing body of evidence suggesting that epigenetic mechanisms mediate the risk for AD.…”
Section: Epigenetic Control Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Besides the nuclear DNA, there is growing evidence that the mitochondrial DNA (mtDNA) could be controlled by epigenetic mechanisms (Hroudová et al, 2014;Blanch et al, 2016;Stoccoro et al, 2017). Several studies have demonstrated the impact of epigenetic modifications on the pathogenesis of neurodegenerative diseases (Urdinguio et al, 2009;Gruber, 2011;Gangisetty and Murugan, 2016;Bassi et al, 2017;Smith and Lunnon, 2017;Berson et al, 2018;Gangisetty et al, 2018;Lardenoije et al, 2018;Lascano et al, 2018;Qazi et al, 2018;Stoccoro and Coppedè, 2018). There is a growing body of evidence suggesting that epigenetic mechanisms mediate the risk for AD.…”
Section: Epigenetic Control Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Transcriptional dysregulation is an early problem in HD and includes alterations in both histone modifications and the function of gene expression regulators. These complications have been extensively researched, and the key findings are summarized by several review articles [56,251,252]. Wild-type HTT interacts with several transcription factors (CREB, SP1, NF-κB, NeuroD, p53, UBF), transcriptional activators and repressors (TAFII130, CA150, NCOR, REST/NRSF, PGC-1α), and nuclear receptors (LXRα, PPARγ, VDR, TRα1) (reviewed in [251,252]).…”
Section: Transcriptional Dysregulation and Related Ptms In Hdmentioning
confidence: 99%
“…Recently, the importance of the delicate balance between PcG and TrxG proteins throughout brain development-particularly embryonic and adult neurogenesis, aging, neuroprotection and neurodegeneration-is being recognized [4][5][6]. The aberrant expression of either PcG or TrxG proteins is beginning to be associated with neurodegenerative disease, such as Alzheimer's, Huntington's and Parkinson's disease [7][8][9]. The current challenge lies in determining the extent to which PcG and TrxG proteins play in the development and progression of these diseases, and if unique complexes exist that could act as early detection biomarkers.…”
Section: Introductionmentioning
confidence: 99%